Training intensity influences left ventricular dimensions in young competitive athletes - Weberruß, Heidi; Baumgartner, Lisa; Mühlbauer, Frauke; Shehu, Nerejda; Oberhoffer-Fritz, Renate (Frontiers in Cardiovascular Medicine, 2022)
Cardiac adaptations to exercise do occur in young athletes, such as increased cardiac chamber dimensions and volumes as well as increased left ventricular wall thickness and left ventricular mass. The heart’s function is either preserved or enhanced but might change to the opposite over time. This study’s aim was to assess structural and functional cardiac adaptations in relation to exercise training time, intensity and performance in young competitive athletes. 404 active children and adolescents (14.23±2.0 years, 97 females) were enrolled in the Munich Cardiovascular Adaptations in Young Athletes Study (MuCAYA-Study). 85 participants were examined twice within one year. Two-dimensional echocardiography was performed to assess left ventricular structure and function. Training time and intensity was measured with the MoMo physical activity questionnaire, maximum aerobic capacity by cardiopulmonary exercise testing and strength with the handgrip strength test. Maximum aerobic capacity had a significant influence on interventricular septal thickness in diastole. Training intensity significantly influenced left ventricular internal diameter in diastole and systole, and left ventricular mass indexed to body surface area. Within one year interventricular wall thickness, relative wall thickness and left ventricular mass, indexed to body surface area and height, increased significantly. Training intensity and aerobic capacity contributed to cardiac adaptations in young competitive athletes, represented by altered structural parameters while cardiac function was still preserved. Within one year, however, structural changes could be observed within the longitudinal sub-sample, accompanied by a decrease in diastolic function.